Membrane-mediated action of the endocannabinoid anandamide on membrane proteins: implications for understanding the receptor-independent mechanism - Medeiros, Djalma; Silva-Goncalves, Laiz da Costa; Brito da Silva, Annielle Mendes; Santos Cabrera, Marcia Perez dos [UNESP]; Arcisio-Miranda, Manoel (Nature Publishing Group, 2017)
Endocannabinoids are amphiphilic molecules that play crucial neurophysiological functions acting as lipid messengers. Antagonists and knockdown of the classical CB1 and CB2 cannabinoid receptors do not completely abolish many endocannabinoid activities, supporting the idea of a mechanism independent of receptors whose mode of action remains unclear. Here we combine gramicidin A (gA) single channel recordings and membrane capacitance measurements to investigate the lipid bilayer-modifying activity of endocannabinoids. Single channel recordings show that the incorporation of endocannabinoids into lipid bilayers reduces the free energy necessary for gramicidin channels to transit from the monomeric to the dimeric conformation. Membrane capacitance demonstrates that the endocannabinoid anandamide has limited effects on the overall structure of the lipid bilayers. Our results associated with the theory of membrane elastic deformation reveal that the action of endocannabinoids on membrane proteins can involve local adjustments of the lipid/protein hydrophobic interface. The current findings shed new light on the receptor-independent mode of action of endocannabinoids on membrane proteins, with important implications towards their neurobiological function.